(untitled) (IAHS Medical Journal, 2026)
Background: Dengue fever, the most prevalent mosquito-borne viral infection, is a recurrent public health threat in Bangladesh. Despite the government’s efforts, dengue outbreaks are on the upswing and people’s knowledge, belief and preventive practices regarding the disease at the rural community level are unclear. The objective of this study was to assess the level of knowledge, attitudes and preventive practices regarding dengue and associated factors among community people of rural Bangladesh. Materials and methods: A cross-sectional survey was conducted involving 127 people using a convenient sampling technique from a village of Sitakunda Upazila of Chattogram, from June to August 2025. Participants responses were collected through face-to-face interviews using a pre-tested structured questionnaire that included information related to socio-demographics, dengue-related knowledge, attitude and preventive practices. Results: Majority 54(42.2%) of respondents age ranged from 28-37 years, Females 68(53.54%) were predominant, 15(11.7%) were graduates, 79(61.7%) were service holders, 40(31.3%) had monthly income more than BDT 50,000, 60(46.9%) came from middle class family. All respondents knew that dengue fever is infectious and 125(98%) knew that untreated dengue fever may lead to death. 90(70.8%) respondents knowledge about dengue fever was good. 94(73.4%) believed that dengue prevention is every ones responsibility and all of them said they will accept dengue vaccine if provided. 100(78.7%) respondents attitude regarding dengue fever was positive. 27(21.1%) cleaned the mosquito breeding sites regularly and 38(29.9%) called the city corporation for fogging. Overall practice was not optimum. Only 51(40%) persons practice regarding prevention of dengue fever was satisfactory. Conclusion: The findings of this study revealed a good level of knowledge and attitude regarding dengue among the respondents. Regarding dengue prevention the overall preventive practices were not satisfactory. This suggests that there is a need for extensive education to increase public awareness on dengue and encourage preventive practices in rural communities of Bangladesh. IAHS Medical Journal Vol 8(2), December 2025; 35-42